2020
DOI: 10.1111/jcms.13033
|View full text |Cite
|
Sign up to set email alerts
|

Reform of the Posting of Workers Regime – An Assessment of the Practical Impact on Unfree Labour Relations

Abstract: The 2018 Amending Directive is the most recent response to the failings of the European Union (EU) legal framework for the posting of workers. This article uses an original case study of workers posted from Serbia via Hungary to Slovakia as a basis on which to assess the practical impact of this latest Directive. We recognize the capacity for EU Member States to do more to protect posted workers than was possible previously. However, we also note significant regulatory omissions relating, in particular, to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The posting of workers is not a problem simply because of the inequalities between old and new Member States, because posting workers affects all Member States. It is a popular form of economic migration, mainly due to the benefits it offers to employers and suppliers, but also to workers, mostly from so-called third countries, who do not need a traditional work permit to enter Member States and generally we can see that temporary work arrangements have increased [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The posting of workers is not a problem simply because of the inequalities between old and new Member States, because posting workers affects all Member States. It is a popular form of economic migration, mainly due to the benefits it offers to employers and suppliers, but also to workers, mostly from so-called third countries, who do not need a traditional work permit to enter Member States and generally we can see that temporary work arrangements have increased [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Our article adds to a growing body of scholarship that stresses the relevance of spatial and geographical concepts in the study of contemporary European labour relations, especially in the context of mobile work (Wagner and Lillie, 2014;Wagner, 2015Wagner, , 2018; van Hoek, 2018;Gumbrell-McCormick and Hyman, 2020;Novitz and Andrijasevic, 2020). The article also follows previous explorations of 'transnational labour law': it contributes to 'problematize and resist the direction of social regulation under globalization' by 'recognizing globalization's asymmetries, and identifying spaces for action' (Blackett and Trebilcock, 2015, p. 4).…”
Section: Introductionmentioning
confidence: 95%
“…Studies also found job displacement in certain sectors such as the construction and meat industry (De Wispelaere and Pacolet, 2017; Lhernould and Palli, 2017; Wagner and Hassel, 2016; Wagner and Lillie, 2014), as well as the development of a dual labour market in some Member States (Doellgast and Greer, 2007; Hassel et al, 2016). Scholars further pointed to regulatory arbitrage on the part of employers and recruitment agencies that exploit the regulatory complexity of posting and the considerable differences between national systems in order to increase their profits (Alberti and Danaj, 2017; Cremers, 2016; Novitz and Andrijasevic, 2020). Research also pointed to higher risks of exploitation and social dumping with the use of posting (Alsos and Eldring, 2008; Cremers et al, 2007; Novitz and Andrijasevic, 2020; Wagner, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars further pointed to regulatory arbitrage on the part of employers and recruitment agencies that exploit the regulatory complexity of posting and the considerable differences between national systems in order to increase their profits (Alberti and Danaj, 2017; Cremers, 2016; Novitz and Andrijasevic, 2020). Research also pointed to higher risks of exploitation and social dumping with the use of posting (Alsos and Eldring, 2008; Cremers et al, 2007; Novitz and Andrijasevic, 2020; Wagner, 2015). Posting is shown to cause pressures on local labour markets due to wage dumping, deteriorating working conditions and outright fraudulent practices such as letter-box companies, abuses with working time and deductions for transport and lodging.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation